Experimental study on bond behavior between heat-damaged recycled asphalt pavement concrete and NSM-CFRP strips. (June 2021) - Barham, Wasim S.; Obaidat, Yasmeen Taleb; Abdelrahman, Bahaa N.
Abstract: In this work, the effect of high temperature on the bond behavior between Recycled Asphalt Pavement (RAP) concrete and Fiber Reinforced Polymer (FRP) was studied. The use of RAP in concrete construction has been developed and utilized recently due to its various economic and environmental features. Nevertheless, very few studies have examined the bonding performance and failure mode between RAP concrete and FRP. A total of 46 asphalt pavement concrete specimens with three different concrete compressive strength were cast and tested under pullout test. The specimens were prepared using different RAP aggregate content and were subjected to elevated temperatures within a range from 23 °C to 600 °C. The heat damaged specimens were repaired using two Near-Surface Mounted Carbon Fiber Reinforced Polymer (NSM-CFRP) strips spaced at 50 mm with three different bonded lengths. According to the experimental results of the pullout test, RAP concrete specimens showed lower bonding strength and slippage than Natural Aggregate (NA) concrete specimens. Furthermore, specimens exposed to elevated temperatures showed a significant decrease in bonding strength and a significant increase in slippage. Results also indicated that as the temperature increased, specimens with high RAP aggregate content failed at higher slippage compared to specimens with low RAP aggregate content with the same compressive strength. Moreover, the relationships between bond load and strain of (CFRP) strips were established and discussed in the results. The failure mode in all specimens was concrete separation.